Strategi Pembelajaran Kontekstual dalam Meningkatkan Pemahaman Konsep Siswa pada Mata Pelajaran IPS - Fuji Ochtaulia; Desy Safitri; Sujarwo (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2025)
Social Studies is often perceived by students as a less engaging subject, partly due to the dominance of lecture-based teaching methods that offer minimal contextual learning experiences. The low level of active student participation in the learning process impacts their conceptual understanding and critical thinking skills. This study aims to evaluate the effectiveness of the Contextual Teaching and Learning (CTL) strategy in improving students’ conceptual understanding in Social Studies through a literature review of various recent research findings and scholarly publications. CTL, as a learning approach that emphasizes the connection between subject matter and students’ real-life contexts, is believed to address these pedagogical challenges. Analysis of the literature sources shows that the consistent implementation of CTL positively contributes to enhancing student engagement, learning outcomes, and the development of critical and analytical thinking skills. Learning that is linked to concrete social experiences encourages students to actively construct meaning, understand interconceptual relationships, and apply knowledge meaningfully in daily life. The conclusion of this review affirms that the CTL strategy is effective in creating a more interactive, meaningful, and deeply comprehensible Social Studies learning process. The novelty of this research lies in its comprehensive synthesis of previous findings, demonstrating that CTL is not only relevant as an innovative teaching method but also holds potential as a systematic approach to pedagogical transformation in Social Studies education at the elementary and secondary levels.